Impact of the COVID-19 pandemic on surgical education and training programs in Latin America: a systematic review - Loza Hernandez, Felipe; Ochoa Lantigua, Pamela; Puga Rosero, Vanesa; Jara Jimenez, Sebastian; Carrera Cajamarca, Mateo; Leon-Rojas, Jose E. (Frontiers in Medicine, 2024)
1) Background: The COVID-19 pandemic posed challenges to surgical training, demanding a balance between theoretical and practical knowledge, especially in Latin American countries. Therefore, our aim was to characterize the challenges faced by surgical education in these countries;(2) Methods: a systematic search was conducted on PubMed, Scopus, and the Virtual Health Library on March 23, 2022, yielding 2838 articles. Articles were filtered by two independent reviewers focusing on the effect of the pandemic in surgical education; (3) Results: a total of 31 articles were selected; 54.83% of surgical programmes reported a reduction in surgical involvement by trainees. First-year residents were the most affected, with some surgical residency programs forced to shift their residents to take care of COVID-19 patients; additionally, in 67.74% of cases, online courses and virtual simulation was implemented. Most of the residents had a positive opinion regarding virtual lectures but considered that their surgical skills were affected; (4) Conclusions: the development of surgical skills was hindered by changes in surgery prioritization, techniques, and a decrease in caseload. The pandemic also caused a reliance on virtual formats for education and patient care. This shift created irregularities in training but increased opportunities for alternate activities.